2014
DOI: 10.1016/j.intell.2014.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Etiological distinction of working memory components in relation to mathematics

Abstract: Working memory has been consistently associated with mathematics achievement, although the etiology of these relations remains poorly understood. The present study examined the genetic and environmental underpinnings of math story problem solving, timed calculation, and untimed calculation alongside working memory components in 12-year-old monozygotic (n = 105) and same-sex dizygotic (n = 143) twin pairs. Results indicated significant phenotypic correlation between each working memory component and all mathema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 44 publications
0
5
0
1
Order By: Relevance
“…g accounted for 49.4% of the variance among the measures. This approach has been used previously (Lukowski et al, 2014) to examine overlapping and unique effects of working memory components and mathematics above and beyond general cognitive ability.…”
Section: Methods – Western Reserve Reading and Math Projectmentioning
confidence: 99%
“…g accounted for 49.4% of the variance among the measures. This approach has been used previously (Lukowski et al, 2014) to examine overlapping and unique effects of working memory components and mathematics above and beyond general cognitive ability.…”
Section: Methods – Western Reserve Reading and Math Projectmentioning
confidence: 99%
“…Previous behavioral genetic studies of individual differences in children on different aspects of executive function and cognitive ability, including working memory, inhibition, processing speed, and naming speed, have consistently found these abilities to be highly heritable, with genetic influences capturing roughly half of the variance when measured with single tasks (Ando, Ono, & Wright, 2001; Haworth et al, 2010; Lukowski et al, 2014; Plomin & Spinath, 2002; Polderman et al, 2006). When measured with latent variables, genetic influences capture up to nearly 100% of the variance (Friedman et al, 2008).…”
Section: Behavioral Genetic Studies Of Cognitive Abilitymentioning
confidence: 99%
“…Although the shared etiology of reading and cognitive abilities is still largely an open question, previous behavioral genetic twin studies of executive functions and cognitive ability more generally offer strong evidence that, to the extent that there is shared variance with reading, it will likely be due to genetic influences. Previous behavioral genetic studies of individual differences in children on different aspects of executive function and cognitive ability, including working memory, inhibition, processing speed, and naming speed, have consistently found these abilities to be highly heritable, with genetic influences capturing roughly half of the variance when measured with single tasks (Ando, Ono, & Wright, 2001; Haworth et al, 2010; Lukowski et al, 2014; Plomin & Spinath, 2002; Polderman et al, 2006). When measured with latent variables, genetic influences capture up to nearly 100% of the variance (Friedman et al, 2008).…”
Section: Behavioral Genetic Studies Of Cognitive Abilitymentioning
confidence: 99%
“…A twin study was conducted to analyze the genetic and environmental influence on cognitive functions and assessed the four cognitive domains of the Wechsler scale and found that the heritability estimate for working memory cognitive functions was ranging from 50-65 percent [14]. The behaviour genetic studies of twins examined the genetic influence on different cognitive functions and concluded that the working memory cognitive abilities were more heritable and influence of genetics capturing half of the variations in cognitive functions of twins [15].…”
Section: Discussionmentioning
confidence: 99%